The meaning of the Instituto Federal Baiano in Local Development of Catu and Teixeira de Freitas (Research, Society and Development, 2018)
The overall purpose of the study was to identify local actors’ understanding of the meaning of the Instituto Federal Baiano within the cities of Catu and Teixeira de Freitas, location in the state of Bahia. With respect to methodology, the Hexagon Model of Regional Development (Boiser, 1996) was used. In its results, the study discovered that the Instituto Federal Baiano is relevant to local development, serves regional vocation and exercises a role in positive change, though it must communicate in the region and act more in order to reach local cultures.